2006
DOI: 10.1523/jneurosci.4317-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Ermin, A Myelinating Oligodendrocyte-Specific Protein That Regulates Cell Morphology

Abstract: Oligodendrocytes form an insulating multilamellar structure of compact myelin around axons, thereby allowing rapid propagation of action potentials. Despite the considerable clinical importance of myelination, little is known about the molecular mechanisms that enable oligodendrocytes to generate their specialized membrane wrapping. Here, we used microarray expression profiling of oligodendrocyte-ablated mutant mice to identify new glial molecules that are involved in CNS myelination. This effort resulted in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
102
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(110 citation statements)
references
References 21 publications
(27 reference statements)
5
102
0
Order By: Relevance
“…We have previously established a mouse line (R26:lacZ/DT-A) enabling us to express DTA in a time-and tissue-specific manner (Brockschnieder et al, 2004). Although this mouse line has proven to be a very useful tool in many different experimental set-ups (Brockschnieder et al, 2006;Gosgnach et al, 2006), we have discovered that homozygous animals develop abnormalities before Cremediated recombination has taken place. In the present study, we provide strong evidence that the observed abnormalities are due to leaky expression of DTA.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously established a mouse line (R26:lacZ/DT-A) enabling us to express DTA in a time-and tissue-specific manner (Brockschnieder et al, 2004). Although this mouse line has proven to be a very useful tool in many different experimental set-ups (Brockschnieder et al, 2006;Gosgnach et al, 2006), we have discovered that homozygous animals develop abnormalities before Cremediated recombination has taken place. In the present study, we provide strong evidence that the observed abnormalities are due to leaky expression of DTA.…”
Section: Discussionmentioning
confidence: 99%
“…First, we compared our database with other studies, primarily the transcriptome database of OLs, neurons, and astrocytes that were isolated from rodent brains (8,(12)(13)(14)(15)(16)(17)(18). Among the 308 proteins, there were at least 111 proteins in our myelin proteome whose mRNA or protein was expressed by OLs (Fig.…”
Section: Protein Identification By Sequential 1-dimensional Page and mentioning
confidence: 99%
“…Many of these transcripts are expressed at higher levels in OL-rich white over gray matter, shown as fold enrichment (i.e., W/G ratio). In addition, to help ascertain the cellular origins of the proteins identified in our proteome, the relative enrichment of their transcripts in purified OLs (red squares in column O), neurons (column N), or astrocytes (column A) was determined through analysis of the transcriptome database of Cahoy et al (8) and other studies (12)(13)(14)(15)(16)(17)(18) of OLs (tan squares in column O). Comparison of the identified proteins in this study with other myelin proteomes (4 -7) has confirmed more than 50% of the identified proteins and revealed the presence of 163 additional proteins in myelin that have not previously been reported in any other proteome (column U).…”
Section: Protein Identification By Sequential 1-dimensional Page and mentioning
confidence: 99%
“…Oligodendroglial process network formation, characterized by the generation and remodeling of higher order branches and interconnections, is initialized by well-coordinated changes in the organization of the actin cytoskeleton (Wilson and Brophy, 1989;Richter-Landsberg, 2000;Song et al, 2001;Liu et al, 2003;Jiang et al, 2005;Williams et al, 2005;Brockschnieder et al, 2006;Nielsen et al, 2006). In non-process bearing, migratory cells such actin cytoskeletal changes are to a large extent controlled by two interdependent mechanisms: 1) modifications of the extracellular environment and 2) the recruitment, retention and dissociation of molecules from focal adhesions, i.e.…”
Section: Introductionmentioning
confidence: 99%